Review on Film Coating Techniques for Ferrous Ascorbate and Folic Acid Tablets - Rohan Jangid; Manmohan Sharma; Anil Ahuja; Ashok Kumar (Asian Journal of Pharmaceutical Research and Development, 2025)
Tablets containing Ferrous Ascorbate and Folic Acid are widely used to prevent and treat iron and folate deficiencies, which are common in India. However, these active ingredients face challenges such as poor stability, metallic taste, and sensitivity to environmental factors. Film coating techniques are employed to overcome these issues by improving stability, masking unpleasant taste, enhancing appearance, and controlling drug release. This review discusses traditional and modern coating methods, including sugar coating, polymer film coating, enteric coating, ready-to-use systems, and natural polymer coatings. It also highlights coating materials, process parameters, and evaluation methods, providing insights for producing high-quality, patient-friendly tablets.